Working experience and entrepreneurship - Borda Olaechea, Arianna (Universidad ESAN, 2018)
Entrepreneurship has become increasingly attractive as a career path for people entering the labor market and more students aim to become entrepreneurs. Some of these students will try to start their own businesses right after finishing their studies but others, want to have some working experiences first to gain knowledge, skills and the resources necessary to start their own business. This study wants to investigate what are the best working experiences for a student who wants to become an entrepreneur in terms of experience, skills acquired, resources, etc. We conducted an exploratory research based on multiple case studies. Data collection was done through in-depth semi-structured interviews, and case studies were chosen through purposeful sampling. In this research we were able to obtain valuable information and insight on how previous working experiences influenced entrepreneurs and helped them achieve success. We were able to analyze their attitudes towards working experience and entrepreneurship, the influence of their previous work experiences, what specific work experiences they believe are most beneficial, the specific skills they believe are most important and their views on whether entrepreneurs should be generalist or specialists. All three of our case studies agreed that their previous working experience influenced and benefited them greatly. Moreover, they all agree that all experiences no matter in what position, area or sector are beneficial, they also mention that having working experience in the same industry is most valuable.
Keywords: Espíritu de empresa; Desarrollo de la carrera; Mercado de trabajo; Estudios de casos; https://purl.org/pe-repo/ocde/ford#5.02.04